Shiva Linga in the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
The centre of the rangamandapa (open type of pillared hall) has a low-raised platform with pillars that support the central ceiling. Presently, a Shiva linga without a yonipatta (womb-shaped base for the linga) is placed at the center of this square platform. The Shiva linga may have been a later addition to the original design of the rangamandapa.